Infliximab reverses inflammatory muscle wasting (sarcopenia) in Crohn's disease. Issue 5 (8th January 2015) - Subramaniam, K.; Fallon, K.; Ruut, T.; Lane, D.; McKay, R.; Shadbolt, B.; Ang, S.; Cook, M.; Platten, J.; Pavli, P.; Taupin, D.
Summary Background Muscle wasting or sarcopenia arising from chronic inflammation is found in 60% of patients with Crohn's disease. Transcriptional protein NF‐κB reduces muscle formation through MyoD transcription and increases muscle breakdown by proteolysis. Aim As TNF is a potent activator of NF‐κB, and anti‐TNF agent infliximab (IFX) prevents NF‐κB activation, to determine whether or not Crohn's patients treated with IFX gain muscle volume and strength. Methods We performed a prospective, repeated‐measures cohort study in adult Crohn's disease patients with an acute disease flare. Patients were instructed not to vary diet or activity. Concomitant medications were kept stable. At week 1 (pre‐treatment), week 16 (post‐IFX induction) and week 25 (post‐first IFX maintenance dose), we assessed (i) MRI volume of quadriceps femoris at anatomical mid‐thigh; (ii) maximal concentric quadriceps contractions strength at three specific speeds of contraction; (iii) physical activity by validated instrument (IPAQ); (iv) Three‐day food record of intake and composition (food‐weighing method); (v) Serum levels of IL6. Results Nineteen patients (58% female; mean age 33.2 ± 10.7 years) were recruited. IFX increased muscle volume in both legs from baseline (right, 1505 cm3) to week 25 (right, 1569 cm3; P = 0.010). IFX also increased muscle strength in both legs from baseline (right 30°/s, 184.8 Nm) to week 25 (right 30°/s, 213.6 Nm; P = 0.002). Muscle volume gain correlated with male gender (P = 0.003). Significant gains in muscle volume and strength were unrelated to prednisolone use. Serum IL6 levels decreased by week 25 (P = 0.037). Conclusion The anti‐TNF agent infliximab reverses inflammatory sarcopenia in patients with Crohn's disease.